Discrepant myocardial microvascular perfusion and mechanics after acute myocardial infarction: Characterization of the "Tako-tsubo effect" with real-time myocardial perfusion contrast echocardiograph. (1st February 2019) - Qiu, Qiong; Abdelghany, Mahmoud; Subedi, Rogin; Scalzetti, Ernest; Feiglin, David; Wang, Jingfeng; Liu, Kan
Abstract: Background: In patients with acute anterior myocardial infarction (MI), sometimes an "apical ballooning" contractile dysfunction pattern that exceeds factual myocardial injury is identified in the ventriculography and bedside echocardiography. The hemodynamic consequences/sequela of this "Tako-tsobu effect" has not been well delineated. Of note, this anatomic imaging finding often misleads frontline physicians who assume reciprocal causation of persistent cardiac pump failure and ventricular pressure overload. Methods and results: Using real-time myocardial perfusion contrast echocardiography (MCE), we investigated myocardial (microvascular) perfusion in 60 patients after acute MI and coronary revascularization. Twenty-eight percent of the studied patients showed significantly mismatched myocardial perfusion and contractile defects. In these patients, an integrated imaging assessment with coronary angiography/ventriculography, deformation echocardiography, and MCE proved that the myocardial mechanic abnormalities significantly exceeded the defected perfusion areas. Compared with 72% of the patients without perfusion-contractility mismatch, apparently worse systolic functions (left ventricular ejection, wall motion score, and systolic longitudinal strain) in these patients did not change diastolic ventricular filling pressures (E/E′ and E/A) or hemodynamic consequences/adverse events. Both systolic and diastolic functions in patients with perfusion-contractility mismatch appeared to be comparable with those in patients with Tako-tsubo syndrome. Conclusions: Real-time MCE identifies discrepant myocardial microvascular perfusion and mechanics in patients with acute MI. The "Tako-tsubo effect" in patients with perfusion-contractility mismatch does not cause diastolic filling pressure change or worse hemodynamic consequence/cardiac event. Highlights: "Tako-tsobu effect" in myocardial infarction results in an assumption of reciprocal causation of pump failure and ventricular pressure overload. Myocardial perfusion echocardiography identifies discrepant myocardial microvascular perfusion and mechanics in "Tako-tsobu effect". "Worse" systolic dysfunctions in patients with "Tako-tsobu effect" do not deteriorate hemodynamics or increase adverse cardiac events. Identifying discordant changes between ventricular contractile function and filling pressure helps post-myocardial infarction management.